Development of a dynamics-based model for analyzing strategic water–environmental conflicts: systems thinking instead of linear thinking. Issue 1 (23rd November 2021) - Shahbaznezhadfard, Mohsen; Yousefi, Saied
Abstract: A new evolution in graph modeling for conflict resolution (GMCR), a robust methodology for conflict resolution, is presented in this research to incorporate the systems thinking concept into the conventional paradigm of GMCR so that the dynamic nature of water–environmental conflicts can be modeled, and better outcomes obtained. To achieve this objective, a methodology is developed in three phases: static, dynamic, and outcome-based analyses. To develop the methodology, the Tigris–Euphrates basin conflict in the Middle East over the past 30 years, as a real-life case study, is used to show the robustness and capabilities of the proposed approach. Finally, a sustainable resolution to the current conflict is proposed, and the results are discussed. The proposed methodology benefits from improving the existing and often static-based conflict resolution developments by considering the dynamic nature so that the true root causes of complex conflicts are addressed, better strategic insights achieved, and comprehensive resolution provided. HIGHLIGHTS: A new method was developed to study the dynamics of water–environmental conflicts. The water conflict of the Tigris and Euphrates basins was studied using the developed methodology. The results showed this conflict with the current trend will take a destructive path in the future. A suitable management platform was proposed to take the conflict off the destructive path and create a sustainable development.